Losing Employment: At-Risk Employed Vocational Rehabilitation Applicants with Vision Loss. (September 2018) - Crudden, Adele; McDonnall, Michele C.; Sui, Zhen
Introduction: Recent U.S. legislation supports vocational rehabilitation efforts to maximize employment and community integration of persons with disabilities by providing job retention and career advancement services. The study presented here investigated employed persons with visual disabilities who applied for vocational rehabilitation services. Methods: The sample included 4, 499 competitively employed vocational rehabilitation applicants from the FY2015 RSA-911 report. Logistic regression was used to identify consumer characteristics and vocational rehabilitation services associated with losing competitive employment. Results: Employed applicants tended to receive assessment, counseling and guidance, diagnosis and treatment, and rehabilitation technology. Characteristics that put employed applicants at increased risk of losing their jobs included being female, having a secondary disability, working fewer hours, having less education, or having a previous unsuccessful vocational rehabilitation employment outcome. There was a significant interaction between vocational rehabilitation case length and age: those served for longer periods were more likely to lose employment, particularly older consumers. Consumers who received short-term on-the-job support, diagnosis and treatment of impairments, or rehabilitation technology services were more likely to retain competitive employment. Discussion: When developing rehabilitation plans for employed applicants, counselors may identify and attempt to provide services to address factors that put consumers at an increased risk of losing employment. Part-time employment at application is one risk factor that requires increased attention. Implications for practitioners: Prompt service delivery is an important factor in facilitating job retention. Increased efforts to maintain consumer contact and motivation may influence the likelihood of job retention among employed applicants.